Chlorido{4-chloro-2- (2-morpholinoethyl)iminomethyl phenolato-kappa N-3,N ',O}copper(II) - Hisham, N.A.I.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The Cu-II atom in the title compound, [Cu(C13H16ClN2O2)Cl], exists in a distorted square-planar coordination environment as the deprotonated Schiff base chelates to the Cu-II atom through three atom sites. In the crystal structure, adjacent molecules are linked by a Cu center dot center dot center dot Cl [3.011 (1) angstrom] bridge, generating a linear chain running along the b axis of the orthorhombic unit cell.